2007
DOI: 10.4028/www.scientific.net/kem.344.939
|View full text |Cite
|
Sign up to set email alerts
|

Economical and Ecological Benefits of Process-Integrated Surface Structuring

Abstract: Properties and functional behavior of modern products are strongly influenced by their surface characteristics - like their appearance and haptics as well as their optical, tribological and fluidic performance [1]. In present production processes these functional features are mostly generated by surface treatment processes (e. g. grinding, etching, coating). In contrast to these costintensive and complex off-line sequences rolling provides an opportunity to apply functional structures on sheet metal products u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The strain values were evaluated from the thickness reductions in the Al sheets using ϵ = ln (h ms /h dp ), where h dp is the average thickness of the deformed metallic sheet. Figure 8(a) shows the flow stress and strain data, and the curve fitted assuming shifted power-law hardening σ = a(ϵ-b) c [39,43,44]. The constants a, b and c and the equation are displayed in the inset of figure 8(a).…”
Section: Finite Element Modelling Of Formation Of Micro-dimplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The strain values were evaluated from the thickness reductions in the Al sheets using ϵ = ln (h ms /h dp ), where h dp is the average thickness of the deformed metallic sheet. Figure 8(a) shows the flow stress and strain data, and the curve fitted assuming shifted power-law hardening σ = a(ϵ-b) c [39,43,44]. The constants a, b and c and the equation are displayed in the inset of figure 8(a).…”
Section: Finite Element Modelling Of Formation Of Micro-dimplesmentioning
confidence: 99%
“…The roller and blank were driven with angular and linear velocities in accordance with the experiments. The coefficient of friction between the aluminium sheet and steel in the FE simulations was specified as 0.2 [35,39,44,46]. The flow stress data following the power-law behaviour in figure 8(a) was used in a tabular form to define the material behaviour in numerical simulations.…”
Section: Finite Element Modelling Of Formation Of Micro-dimplesmentioning
confidence: 99%
“…Bringing riblet structures into metal surfaces has been investigated in previous publications [7,8,9,10,11,12]. As riblet efficiency has to be in accordance with producibility, semi-circular riblets seem to be a reasonable choice (Fig.…”
Section: State Of the Artmentioning
confidence: 99%
“…An enhancement of product functionality had been developed by specific functional surface structures with micro-structure. 1,2 Micro-structured surface can also improve ecologic aspects in production processes and reduce the resistance of material, improving wear resistance and mechanical properties. Several authors [3][4][5] reported using special biological surface microstructures with super-oleophobic characteristics, solved the problems associated with oil adhering to pipeline surfaces, and subsequently contributed to reducing the marine oil pollution.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of machining, many high precision microstructures on the rolls can be machined. 2,19 During rolling, it is difficult for aluminum alloy sheet having poor flowability because the literature 18 showed riblet form filling up to 70%, that required rolling high quality filling grooves on the surface improve furtherly. In order to meet the requirements of the better grooves on the surface, it is necessary to improve the flowability of aluminum alloy.…”
Section: Introductionmentioning
confidence: 99%